Associations of Changes in Religiosity With Flourishing During the COVID-19 Pandemic: A Study of Faith Communities in the United States - Jacobi, Christopher Justin; Cowden, Richard G.; Vaidyanathan, Brandon (Frontiers in Psychology, 2022)
This study explored the extent to which perceived changes in religiosity from before to during the COVID-19 pandemic are associated with flourishing. Participants from a diverse set of faith communities in two US metropolitan regions (N=1,480) completed an online survey between October to December 2020. The survey included items capturing perceived changes in four dimensions of religiosity (i.e., importance of religion, frequency of prayer, frequency of religious service attendance, and sense of connectedness to one’s faith community) and a multidimensional measure of flourishing. Based on multilevel regressions, results indicated that self-reported decreases in each dimension of religiosity were associated with lower overall flourishing. This pattern of findings was largely similar for the domains of flourishing, with some variation in the strength of associations that emerged. An increase in frequency of religious service attendance was associated with lower overall flourishing and lower scores on selected domains of flourishing (e.g., mental and physical health), indicating possible evidence of religious coping. Faith communities might have to find ways of supporting members during the challenging COVID-19 period to prevent long-term declines in flourishing.